1997
DOI: 10.1038/ki.1997.219
|View full text |Cite
|
Sign up to set email alerts
|

Thin GBM nephropathy: Premature glomerular obsolescence is associated with hypertension and late onset renal failure

Abstract: Thin glomerular basement membrane (GBM) nephropathy, also called familial benign hematuria, is characterized by chronic hematuria and uniform thinning of the lamina densa of the glomerular basement membrane. It generally holds an excellent renal prognosis. Alport syndrome in early stages can also show attenuation of the GBM; conversely, renal insufficiency has been reported in familial benign hematuria. To discern early Alport syndrome from thin GBM nephropathy, we carried out a prospective epidemiological stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
75
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 12 publications
5
75
0
Order By: Relevance
“…It should be noted that it was suggested that the molecular type of COL4A3/A4 mutations and additional modifier genes are likely to influence the severity of the renal phenotype eventually (35,36,37). Second, hypertension in adults with TBMN was reported previously and is likely to worsen the general prognosis of affected patients (13,25). Third, clinical reports suggest that individuals with TBMN must be viewed to be in a pool of patients who generally display above-average rates of mortality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It should be noted that it was suggested that the molecular type of COL4A3/A4 mutations and additional modifier genes are likely to influence the severity of the renal phenotype eventually (35,36,37). Second, hypertension in adults with TBMN was reported previously and is likely to worsen the general prognosis of affected patients (13,25). Third, clinical reports suggest that individuals with TBMN must be viewed to be in a pool of patients who generally display above-average rates of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Although TBMN is considered to have a good prognosis owing to a nonprogressive nephropathy, numerous hints in the literature suggest a reduced lifespan in affected individuals. First, the possibility that TBMN may not be benign in terms of ultimate prognosis has been considered before (13,14,18,30,25), and ESRD similar to that seen in AS was reported in adults with heterozygote COL4A3/A4 mutations (occasionally also referred to as "autosomal dominant Alport syndrome") (15,34 -37). It should be noted that it was suggested that the molecular type of COL4A3/A4 mutations and additional modifier genes are likely to influence the severity of the renal phenotype eventually (35,36,37).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16,19,20 A small proportion may also develop renal insufficiency due to glomerular disease. [21][22][23] As a result, some form of patient follow-up is recommended after negative initial evaluation for AMH.…”
Section: Evaluation Of the Upper And Lower Urinary Tractsmentioning
confidence: 99%